Time Dilation and Special Relativity (Global Journal of Science Frontier Research, 2022)
The presentation and defination of Time as a concept in the Theory Special Theory of Relativity is remarkably difference to that of Time in the Theory of Classical Mechanics. In Special Relativity, Time is considered as the fourth dimension in the fabric of spacetime. However, the presentation of time as such, can be argued upon, as time can be defined as a method of defining events relative to one another. This paper provides an insight into Time Dilation details of its occurrence, and the controversial representation of time.